Effects of repeated use of post-exercise infrared sauna on neuromuscular performance and muscle hypertrophy - Ahokas, Essi K.; Hanstock, Helen G.; Kyröläinen, Heikki; Ihalainen, Johanna K. (Frontiers in Sports and Active Living, 2025)
PurposeThe aim of this study was to investigate whether regular use of infrared sauna (IRS) after training can promote neuromuscular performance and positive changes in body composition during a 6-week training period.MethodsForty female team sport athletes were pair-matched into two groups: IRS (n = 20) and control (CON; n = 20). Physical performance tests, body composition and hypertrophy measurements (dual-energy x-ray absorptiometry and ultrasound of m. vastus lateralis) were performed PRE and POST a 6-week strength and power training period, involving 2–3 sessions per week. Performance tests included a 20 m sprint, squat jump (SJ), countermovement jumps with body weight (CMJ) as well as with 15, 25, and 50% additional load (CMJ15%, CMJ25%, and CMJ50%), and a maximal isometric leg press (MVC). Participants in the IRS-group used IRS (10 min, 50℃) after training three times per week.ResultsTraining improved neuromuscular performance and muscle hypertrophy in both groups (p < 0.05). Following the discovery of an interaction effect for CMJ15% height (p = 0.002) and peak power (p = 0.010), post hoc tests revealed higher jump height POST-IRS (p = 0.006) and PRE-CON (p = 0.023) compared to PRE-IRS, and higher peak power POST-IRS (p = 0.002) compared to PRE-IRS. Furthermore, an interaction effect was observed for 5 m split time of the 20 m sprint (p = 0.020), but no differences were found between groups and timepoints. There were no interactions for the hypertrophy measures.ConclusionIncorporating post-exercise IRS bathing does not significantly impact hypertrophy gains, but might boost long-term power production capabilities.